2011
DOI: 10.2298/bah1103201z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fatty acid composition and cholesterol content of goat colostrum

Abstract: The purpose of this paper is to detect any changes in fatty acid and cholesterol content of goat colostrum in the period of 0-72 hours after kidding. For that purpose, samples of colostrum from 16 goats, belonging to local populations in north-eastern Romania where collected. Samples were preserved by freezing and then subjected to chemical analysis. Preparation of solutions for fatty acids analysis was based on the principle of methylation, by combining alkaline methylation (NaOCH3/MeOH) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The concentration of cholesterol in mature goat milk was lower (11.64 ± 1.09 mg/dL) than those reported by Strzałkowska et al (2006) and Zaharia et al (2011). It was also shown that ChC in colostrum (9.43 mg/dL) was lower than in mature milk (15.68-19.10 mg/dL) [87,88].…”
Section: Nutritional Value and Health-promoting Properties Of Cholesterol Concentration In Milkmentioning
confidence: 78%
“…The concentration of cholesterol in mature goat milk was lower (11.64 ± 1.09 mg/dL) than those reported by Strzałkowska et al (2006) and Zaharia et al (2011). It was also shown that ChC in colostrum (9.43 mg/dL) was lower than in mature milk (15.68-19.10 mg/dL) [87,88].…”
Section: Nutritional Value and Health-promoting Properties Of Cholesterol Concentration In Milkmentioning
confidence: 78%
“…The actual problem is to justify the approaches and development of the technology of stabilization of composition and native properties of products of a lactation of goats when in storage, taking into account seasonal nature of production of these types of livestock production and their biochemical features [9][10]. An important task within this problem is to widespread the introduction of sublimation drying in a food production.…”
mentioning
confidence: 99%